Test-language effects in bilingual education: Evidence from CLIL classes in Germany. (October 2021) - Canz, Thomas; Piesche, Nicole; Dallinger, Sara; Jonkmann, Kathrin
Abstract: In the last decades, many bilingual programs such as content and language integrated learning (CLIL) have emerged. A crucial question in CLIL is whether to assess students' content-subject knowledge in the common language or the dominant language of instruction. In two experimental field studies with N = 361 6th-graders and N = 703 8th-graders, we investigated test-language effects and their moderation by CLIL-experience, language background, instructional language use and item format. In both studies, students' achievement was higher when items were presented in the common language. This effect was less pronounced in experienced CLIL-learners and for multiple-choice than cloze-test items. Moderation effects of language background were only partially and for instructional language use not statistically significant. The results show that using the dominant language of instruction to assess content-subject knowledge in bilingual education might underestimate students' learning and that test-language and item-format effects need to be considered. Highlights: In bilingual education assessment, test-language effects occurred. In bilingual learning, there is an advantage for L1 as test language. Test-language effects are more pronounced in CLIL novices than in advanced CLIL-learners. Test-language effects are stronger for cloze tests than for multiple choice items.